Analisis Struktur Pasar dan Daya Saing Ekspor Crude Palm Oil (CPO) Indonesia di Pasar Dunia - Oskarlina, Nia; Karya, Detri; Amin, Azharuddin M (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Crude palm oil (CPO) is a strategic commodity with significant export potential for Indonesia. This study aims to analyze (1) the structure of the Indonesian CPO market in the global market, (2) comparative advantages, and (3) competitive advantages over Malaysia in relation to major export destination countries. The research used a literature study method with secondary data during the period 2014–2023 on five major export destination countries, namely India, the Netherlands, Italy, Spain, and China. Data analysis includes market share and concentration ratio methods (market structure), RCA, RSCA and TSI (comparative advantage), as well as ECI, CMSA, and EPD (competitive advantage). The results of the study show that the CPO market structure is a tight oligopoly with a CR5 value of 82.50% in Indonesia and 85.46% in Malaysia, and an HHI of 4,421.88 and 3,802.53, respectively. Indonesia and Malaysia have high comparative advantages (RCA>1; RSCA>0), and Indonesia consistently ranks as a net exporter (TSI=0.9996). Indonesia's competitive advantage remains limited because not all destination countries have an ECI value > 1, with CMSA performance that is relatively lower than Malaysia's. Based on the EPD, Indonesia's export position is in the lost opportunity category (India, China) and retreat category (Netherlands, Italy, Spain), while Malaysia is in the retreat (India and the Netherlands) and lost opportunity quadrant (Italy, Spain, and China).